Approaches to Designing a Wireless Sensor Network Node for IoT Solution - Sukov, A.; Zayanchukovsky, A.; Olizarenko, V.; Galkin, P. (ХНУРЕ, 2020)
The object of the research is the hardware component for building a test platform for wireless sensor networks. The aim of the work is to develop a software and hardware test platform for wireless sensor networks. As a result of the analysis, the node structures, wireless sensor network modules, CC2530 peripherals were analyzed. A module based on the CC2530 PA was chosen as the hardware. Given to optimize the structure of the node for as one of approach to designing a wireless sensor network node. Also given report about difference in approach to designing nodes and uses areas. All developments will receive life in the educational process of the department. Sample production is already underway.
Keywords: Wireless Sensor Network; IoT Solution; Approaches; IoT; Approaches to Designing; CC2530